Debate divinity of Jesus & crucifixion ([s.l. : s.n.])
A debate between Dr. Robert Douglas and Al-Hafiz Yusuf Buckas about the crucifixion of Jesus Christ
Title from container
Keywords: Jesus Christ -- Crucifixion; Easter; Jesus Christ